2019
DOI: 10.1177/0145561319840902
|View full text |Cite
|
Sign up to set email alerts
|

Optokinetic Analysis in Patients With Spontaneous Horizontal Gaze-Evoked Nystagmus Without Radiological Neuropathology

Abstract: Gaze-evoked nystagmus is not rare among those who have acute balance problem and may indicate a cerebellar dysfunction that is associated with a broad spectrum of disorders. The aim of this study is to analyze optokinetic response in those patients. Eleven males and 7 females (age range: 25-60, 42.5 [9.75]) with gaze-evoked nystagmus were analyzed with optokinetic test (Micromed Inc). Nystagmus was elicited by a stimulator light spot moving across the patient’s visual field at a target speed of 30 degree/secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
3
2
Order By: Relevance
“…In comparison to studies performed in patients with cerebellar disease, GEN eye drift velocities found in our study were at the low end of reported velocities (1-24 • /s) (9,11,23,26,27). Eye drift velocities of RN in patients with cerebellar disease were rarely reported.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…In comparison to studies performed in patients with cerebellar disease, GEN eye drift velocities found in our study were at the low end of reported velocities (1-24 • /s) (9,11,23,26,27). Eye drift velocities of RN in patients with cerebellar disease were rarely reported.…”
Section: Discussioncontrasting
confidence: 85%
“…We demonstrate that even persistence of GEN over time is not a solid sign for being pathological. While prior reports described GEN to be pathological if persistent over 20 s (27,29), we observed that (although the velocity of drift decreased during prolonged eccentric gaze) GEN commonly persisted for the duration of 30 s (in 64-100% of subjects depending on gaze eccentricity). Furthermore, while the velocities found in our study were generally at the low end of ranges presented in prior studies in patients, these results still indicate that certain cases might have been wrongly identified as pathological.…”
Section: Discussioncontrasting
confidence: 74%
“…Furthermore, to not miss a certain central sign, we included vertical nystagmus and direction changing GEN in our screening system which are known to be the nystagmus occurring by disorganization of neural integrator or impairment of cerebellar gaze-holding mechanism. 21,22) In our study, sensitivity and specificity of presence of nystagmus after head shaking test (positive HSN) were 84.8% and 51.3%, respectively. They were significantly different from previous studies of HSN, 14,15) which proposed lower sensitivity of HSN for detecting VS. Humphriss, et al 14) have reported a sensitivity of 22% as a result of 22 positive HSN among 102 subjects.…”
Section: Discussionmentioning
confidence: 47%
“…[14][15][16][17][18][19][20] Herein, the authors devised a nystagmus based screening system (NBSS) for VS in ASNHL patients. The NBSS is composed of four different types of nystagmus: vertical spontaneous nystagmus (SN) and direction changing gaze evoked nystagmus (GEN), which are previously studied central sign nystagmus, [21][22][23][24] and two types of HSN which firstly show ipsilesional nystagmus after head shaking. We also compared the sensitivity and specificity of NBSS with ABR and confirmed the usefulness of the new screening system.…”
Section: Introductionmentioning
confidence: 99%
“…According to Yetiser et al, optokinetic testing can detect evidence of central disorders, particularly cerebellar damage and brainstem damage. Because none of the patients in this study had postoperative abnormalities, it can be concluded that cochlear implantation did not result in central lesions (51). These could be excluded preoperatively as a cause of vertigo among all patients in vertigo classes 2 and 3.…”
Section: Optokinetic Testingmentioning
confidence: 64%